THE RELATIONSHIP BETWEEN QUARTER-LIFE CRISIS AND THE LEVEL OF RELIGIOSITY IN FINAL-YEAR STUDENTS - Putri, Isabella Cantika; Suryati, Suryati; Fitri, Hartika Utami (LP2M IAI Al-Khairat Pamekasan, 2024)
This study aims to determine whether there is a relationship between quarter-life crisis and religiosity. This study used a quantitative approach with a correlational type of research. The population in the survey was final-year students of the Faculty of Da'wah and Communication, which amounted to 638 students. From the sampling technique used using Slovin, there was a sample of 87 students. This study takes a quantitative approach with correlational research that aims to determine how two variables are connected. This field study uses questionnaire-based data collection methods and documentation, with 25 statement items from each instrument. The design of this study is to correlate Pearson product moments. The results showed that the average student experienced a quarter-life crisis and a moderate level of religiosity. Meanwhile, the Correlation test results show a strong relationship between the quarter-life crisis and the level of religiosity in final-year students of the Faculty of Da'wah and Communication. The relationship is determined based on the interpretation of the correlation coefficient, which is in the range of 0.60-0.799—testing the data hypothesis in research that has been done, where the higher the quarter-life crisis experienced, the higher the level of religiosity in students.